The golden age of Czech spas : old photographs tell their stories = Tschechische Kurorte zur Kaiserzeit - Scheufler, Pavel (2019)
The world of spas at the end of the Austrian-Hungarian Empire, when the emperor, the aristocracy and famous visitors from all aver Europe would take the waters, is long gone. Elegant ladies and gentlemen would come to these towns for health, diversion, amusement and tranquility. This countryþs many smaller and lesser-known spas offered seclusion and relaxation, while the beautiful promenades, cafés and casinos of Karlovy Vary, Mariánské Lázne and Frantiskovy Lázne offered entertainment, conviviality and romance. All of this was captured by photographers whose pictures can now take us back to a lost world.00These pictures guide us through spa towns in an age when Austro-Hungarian emperorþs portrait still hung in schools and public buildings. The individual photographs in this book all have stories to tell, and they present what the writer Stefan Zweig described as ?an ordered world with definite classes and calm transitions, a world without haste?.